Fabrication of vertical side-wall submicron emitter for heterojunction bipolar transistors - Radhakrishnan, K. (2008)
In this investigation, several dry etching processes have been systematically studied for submicron emitter formation for metamorphic heterojunction bipolar transistor (MHBT) devices. CH4/H2/O2 chemistry is shown to offer better side wall etch profile and smoother surface compared to other gas mixtures. Optimized HBT emitter etching process is developed by combining the plasma dry etching and the wet etching techniques. Submicron sized (0.6 μm × 20 μm) emitters have been demonstrated using direct electron beam lithography. RF performance of the MHBT devices (1.0×20 μm2) fabricated using the new dry-wet etch combination demonstrates fT and fMAX values of 92 GHz and 122 GHz, respectively. These values are higher than HBTs fabricated using all-wet-etch process.